DIFFUSE LARGE B CELL LYMPHOMA - Krisna Murti (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Diffuse large B cell lymphoma is a neoplasm arising from B lymphocytes and having a diffuse growth pattern. The nuclei cells showed a medium or similar or larger than the sizes of normal macrophages. This entity is the most common type of non-Hodgkin lymphoma (NHL) with incidence 30-40% from all NHL types. In Indonesia DLBCL cases was 68.2%, much higher than that in western countries (37%) and slightly higher than in other Asian countries (30-60%). Another data showed that in Indonesia there was 16.125 new NHL cases in 2020. This entity has diversity of molecular pathogenesis causes DLBCL showed some heterogeneity and similarities of clinical sign and symptoms, morphology and immunopheno types with other non-Hodgkin lymphomas. Therefore, some other molecular analysis such mutation events should be performed to achieve a correct diagnosis. All clinical data, morphologic immunhistochemical foundings have to be collected and analyzed and some additional molecular examination should be also conducted such as FISH analysis, PCR-based assay to exclude differential diagnosis. Some patients can be cured with a standard regimen Rituximab-Cyclophosphamide, Doxorubicin, Vincristine, and Prednisolone (R-CHOP). However, 40% of patients is refractory or relapse.